Body condition index in breeding black iguana females (Ctenosaura pectinata) in captivity - Arcos-García, José Luis; Núñez Ordaz, Jesús; García Grajales, Jesús; Rueda Zozaya, Rocío del Pilar; Romero, Héctor Santiago; López Pozos, Roberto (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
The body condition index is a measure that attempts to describe energy storage compared to body length. This research was carried out with the aim of obtaining a body condition index in Ctenosaura pectinata. We used 40 adult females distributed between two groups. The iguanas were fed with four types of commercial food. They were also weighed in grams, their body lengths were measured in centimeters (total, snout-vent and head), body diameters were measured in centimeters (tail base, hip, leg, and pelvis) and body volume was measured in milliliters. Descriptive statistics were performed and variables were checked for normality. A Pearson correlation analysis was carried out to identify any related variables. A body condition index classification was obtained from the mean value and standard deviation (I: 2S-µ, II: S-µ, III: µ+S and IV: µ+2S) and a prediction equation for volume was obtained by Stepwise analysis. The body condition index turned to be highly accurate (r=0.98, pË‚0.0001). A body condition index classification in black iguana (Ctenosaura pectinata) was established, which will be useful for monitoring the body reserves of the species. Highlights: Body condition is a method to evaluate the reserves of animal fat tissues in their productive and reproductive states. In reptiles body conditions affects the females survival, egg size, and brood size, but it is not known in black iguana due to lack of information. Reproductive females black iguana classified as I (lean) and IV (excessively corpulent) presented non-reproductive conditions in captive condition.